If it's not what You are looking for type in the equation solver your own equation and let us solve it.
448=-7(-9x+17)
We move all terms to the left:
448-(-7(-9x+17))=0
We calculate terms in parentheses: -(-7(-9x+17)), so:We get rid of parentheses
-7(-9x+17)
We multiply parentheses
63x-119
Back to the equation:
-(63x-119)
-63x+119+448=0
We add all the numbers together, and all the variables
-63x+567=0
We move all terms containing x to the left, all other terms to the right
-63x=-567
x=-567/-63
x=+9
| 6x+72=3x | | 3(x+1)=5x-1,x | | 20=5p | | (7x+16)+(3x-6)=180 | | (3x−6)+(7x+16)=180 | | U=-2+2a | | 7x-114=-2x+57 | | 40-x=20 | | 360=59-x=9x/2+15 | | 7x=—5 | | -x^2-9x=2x-6 | | 13=-2k | | -4/7k=-26 | | 2/11m+(16)=4+6/11m | | 4=9-3(2x+1)+5x | | 59-x=9x/2+15 | | (2/11)m+(16)=(4)+(6/11)m | | 3x/18=108 | | 2m=18.8 | | (2/11)m+(16)=4+(6/11)m | | 4=-8+x | | 3x-8=-7+18 | | 77-x=87-2x | | 8+P=x | | 2(b-4)+8=1/2(6b+20) | | (2x-26)+(7x+8)=180 | | 6x+24+8x-12=360 | | X-8=-x-2 | | 8(x+3)=2(4x-3) | | -4(4x-9)=20 | | 0=-1+x | | 3(6-x)=6x-17-2x |